Sistema móvil vehicular para mejorar la seguridad a través de la red GSM - Guayaquil Gonzabay, Cristóbal Roberto (2018)
It is admirable the progress of computer systems over the years and the demand for it, always looking for safety as the first point, when connectivity is one of the main fields that has had the greatest push in recent years has been telephony mobile, which every time improves its service so that users have access to data, Wi-Fi, text messages, multimedia messages, music players, television, radio, bluetooth, among many others. According to a publication made by the National Institute of Statistics and Censuses (INEC) at the end of 2015, I publish that of 100 Ecuadorians, 56 of them have an active cell phone, a sum that 5 years ago has grown considerably (Heredia, 2016). The development of information systems, communication and technological undertakings was used as a research line, using the intelligent automation of industrial processes as a sub-line. It is worrisome the high rate of car theft that exists today, it is estimated according to figures that in the last 2 and a half years the police recorded the theft of 13,271 cars nationwide, which is a very high figure that should be treated as much as possible for the well-being of citizens (El Telegrafo, 2017). In the present work, a security prototype was made that allows making live calls, in case of an emergency or attempted robbery, managing as a central point the communication between the vehicle and the client by means of a telephone call and sending in real time a text message affirming what happened with real location by means of GPS.